Collaborative authoring: a case study of the use of a wiki as a tool to keep systematic reviews up to date - Bender, Jacqueline L (Open Medicine Publications, Inc., 2011)
BACKGROUND: Systematic reviews are recognized as the most effective means of summarizing research evidence. However, they are limited by the time and effort required to keep them up to date. Wikis present a unique opportunity to facilitate collaboration among many authors. The purpose of this study was to examine the use of a wiki as an online collaborative tool for the updating of a type of systematic review known as a scoping review. METHODS: An existing peer-reviewed scoping review on asynchronous telehealth was previously published on an open, publicly available wiki. Log file analysis, user questionnaires and content analysis were used to collect descriptive and evaluative data on the use of the site from 9 June 2009 to 10 April 2010. Blog postings from referring sites were also analyzed. RESULTS: During the 10-month study period, there were a total of 1222 visits to the site, 3996 page views and 875 unique visitors from around the globe. Five unique visitors (0.6% of the total number of visitors) submitted a total of 6 contributions to the site: 3 contributions were made to the article itself, and 3 to the discussion pages. None of the contributions enhanced the evidence base of the scoping review. The commentary about the project in the blogosphere was positive, tempered with some skepticism. INTERPRETATIONS: Despite the fact that wikis provide an easy-to-use, free and powerful means to edit information, fewer than 1% of visitors contributed content to the wiki. These results may be a function of limited interest in the topic area, the review methodology itself, lack of familiarity with the wiki, and the incentive structure of academic publishing. Controversial and timely topics in addition to incentives and organizational support for Web 2.0 impact metrics might motivate greater participation in online collaborative efforts to keep scientific knowledge up to date.